Current Perspectives in Mesenchymal Stem Cell Therapies for Osteoarthritis - Baldur Kristjánsson; Sittisak Honsawek (Stem Cells International)
Osteoarthritis (OA) is a degenerative joint disease most commonly occurring in the ageing population. It is a slow progressive condition resulting in the destruction of hyaline cartilage followed by pain and reduced activity. Conventional treatments have little effects on the progression of the condition often leaving surgery as the last option. In the last 10 years tissue engineering utilising mesenchymal stem cells has been emerging as an alternative method for treating OA. Mesenchymal stem cells (MSCs) are multipotent progenitor cells found in various tissues, most commonly bone marrow and adipose tissue. MSCs are capable of differentiating into osteocytes, adipocytes, and chondrocytes. Autologous MSCs can be easily harvested and applied in treatment, but allogenic cells can also be employed. The early uses of MSCs focused on the implantations of cell rich matrixes during open surgeries, resulting in the formation of hyaline-like durable cartilage. More recently, the focus has completely shifted towards direct intra-articular injections where a great number of cells are suspended and injected into affected joints. In this review the history and early uses of MSCs in cartilage regeneration are reviewed and different approaches in current trends are explained and evaluated.